Chairman Workinggroup Kairos and Shipping Research Bureau at UN-hearings on sanctions against South Africa in New York - Nagata, Yutaka,
Chairman Workinggroup Kairos and Shipping Research Bureau at UN-hearings on sanctions against South Africa in New York.